2006
DOI: 10.1583/05-1771.1
|View full text |Cite
|
Sign up to set email alerts
|

Distal Embolism During Percutaneous Revascularization of Infra-Aortic Arterial Occlusive Disease:An Underestimated Phenomenon

Abstract: The embolism phenomenon during infra-aortic interventions is frequent and underestimated. The liberated particles consisted primarily of atheromatous plaque elements and thrombus. The reported data might support the application of a protective filter basket in selected subsets of lesions with a riskier embolic profile and whenever declotting procedures are performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 33 publications
5
105
1
4
Order By: Relevance
“…These results are in line with other lower-extremity case series in which the debris retrieval rates were between 12% and 89% (4,5,10,13). In our experience, lesion characteristics, lesion location, and treatment method were not significantly different between patients in whom debris was and was not retrieved.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in line with other lower-extremity case series in which the debris retrieval rates were between 12% and 89% (4,5,10,13). In our experience, lesion characteristics, lesion location, and treatment method were not significantly different between patients in whom debris was and was not retrieved.…”
Section: Discussionsupporting
confidence: 90%
“…Distal embolization is also a well documented phenomenon in the setting of infrainguinal percutaneous balloon angioplasty, stent placement, thrombolysis, and endovascular atherectomy (3)(4)(5)(6). However, the occurrence of this event has been viewed as largely insignificant (7).…”
mentioning
confidence: 99%
“…Micro-and macrodebris are frequently captured with various embolic protection devices. [62][63][64][65][66] DE requiring further treatment occurs in 2 to 3% of unselected infrainguinal interventions. 67 Its predictors are long occlusions, thrombotic lesions, 67 mechanical thrombectomy, 26 directional atherectomy, 6,65 and laser atherectomy.…”
Section: Procedural Factorsmentioning
confidence: 99%
“…In addition, occlusion of the denovo lesion was a predictor of arterial thromboembolism during EVR. Karnabatidis et al [1] reported that CTO was positively correlated with a larger amount of captured particles (P < 0.05). In addition, histopathological examination of coronary artery CTO [14] showed that the intimal plaque in short-duration CTO was highly fibrotic with calcified lesions, while that in long-duration CTO was harder with more dense calcification.…”
Section: Discussionmentioning
confidence: 96%
“…The reported incidence is up to 98% [1]; however, the reported incidence of thromboembolic events that can be detected on angiography and cause clinical symptoms ranges from 1.6% to 24% [1,2]. Although surgical embolectomy is the classic and standard treatment for the management of thromboembolic complications in the lower extremity, endovascular techniques, including catheter-directed thrombolysis (CDT), percutaneous aspiration thrombectomy (PAT) and mechanical thrombectomy using dedicated peripheral arterial percutaneous thrombectomy devices, are increasingly being used for the removal of arterial emboli and restoration of blood flow [3][4][5].…”
Section: Introductionmentioning
confidence: 99%